2018
DOI: 10.1186/s12885-018-4976-3
|View full text |Cite
|
Sign up to set email alerts
|

Effect of COPD on symptoms, quality of life and prognosis in patients with advanced non-small cell lung cancer

Abstract: BackgroundMany studies have reported the prevalence of chronic obstructive pulmonary disease (COPD) and its effects and prognosis in patients with lung cancer, but few have considered quality of life and survival of patients with lung cancer according to severity of airway obstruction. This study investigated the presence of COPD and the severity of airway obstruction in patients with non-small cell lung cancer (NSCLC), and analyzed how these factors affected symptoms, quality of life, and prognosis.MethodsWe … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
28
0
3

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 46 publications
(37 citation statements)
references
References 28 publications
6
28
0
3
Order By: Relevance
“…At present, there are many reports on the impact of COPD on the prognosis of NSCLC, but opinions are not uniform. Maria Iachina et al showed that the survival rate of NSCLC patients with COPD significantly decreased, and Norihito Omote et al showed that mild to moderate COPD had no significant adverse effect on the prognosis of NSCLC patients . Our meta‐analysis showed that NSCLC with COPD had a poor prognosis, similar to the results of Maria Iachina et al Besides, Maria Iachina contributed significantly to the study, accounting for 67.9% (Fixed effect model), which seemed to be related to the large proportion of the total sample size included and the large proportion of the sample size of NSCLC without COPD.…”
Section: Discussionsupporting
confidence: 82%
See 1 more Smart Citation
“…At present, there are many reports on the impact of COPD on the prognosis of NSCLC, but opinions are not uniform. Maria Iachina et al showed that the survival rate of NSCLC patients with COPD significantly decreased, and Norihito Omote et al showed that mild to moderate COPD had no significant adverse effect on the prognosis of NSCLC patients . Our meta‐analysis showed that NSCLC with COPD had a poor prognosis, similar to the results of Maria Iachina et al Besides, Maria Iachina contributed significantly to the study, accounting for 67.9% (Fixed effect model), which seemed to be related to the large proportion of the total sample size included and the large proportion of the sample size of NSCLC without COPD.…”
Section: Discussionsupporting
confidence: 82%
“…The sample sizes for different studies of NSCLC ranged from 85 to 10 378, with a total number of 14 164, including COPD 2450 and Non‐COPD 9395. 12 case‐control studies were conducted in Korea, Denmark, Japan, the United States and Spain . In terms of diagnosis of COPD, 4 studies used Spirometry, 3 studies used GOLD guideline, 2 studies used American Thoracic Society criteria or European Respiratory Society criteria, 1 studies used Spirometry and/or Computed tomography (CT), 1 studies used Medical record and 1 studies used doctor‐diagnosis …”
Section: Resultsmentioning
confidence: 99%
“…The CMC lung cancer registry registered patients' symptoms, comorbid diseases, quality of life, and smoking history (smoking status, amounts, and cessation duration) through a same questionnaire at the time of lung cancer diagnosis (Supplementary 1). Smoking status was defined as our previous work [10,11]. Current smoker was defined a patient who continued smoking upon diagnosis or stopped smoking less than 1 month before diagnosis of lung cancer.…”
Section: Data Sourcementioning
confidence: 99%
“…We analyzed data of patients from Seoul St. Mary's Hospital and Bucheon St Mary's Hospital among cohort hospitals because their medical charts related to the development of pneumonia were available for review. The CMC lung cancer registry has registered patients' symptoms, quality of life, and accompanying diseases through a common questionnaire at the time of diagnosis [7]. We also collected smoking history including smoking status, pack-year, and duration of smoking cessation.…”
Section: Data Sourcementioning
confidence: 99%